Triangulating Trauma: Constellations of Memory, Representation, and Distortion in Elie Wiesel, Wolfgang Borchert, and W.G. Sebald - William Mahan (Humanities, 2017)
Even today, trauma theory remains indebted to Sigmund Freud’s notion of belatedness: a traumatic event is not fully experienced at the time of occurrence, due to its suddenness and the lack of preparedness on the part of the human subject. In Traumatic Realism (2000), Michael Rothberg invokes the Benjaminian notion of the constellation of representation to address the shortcomings of any singular mode of trauma portrayal. Rothberg likens the realist, modernist, and postmodernist literary modes to the points of view of the survivor, the bystander, and the latecomer, respectively. I combine Rothberg’s typology with insights from trauma theory to analyze Elie Wiesel’s Night, Wolfgang Borchert’s The Man Outside, and W.G. Sebald’s The Emigrants—three texts that represent Rothberg’s literary modes while at the same time problematizing genre. Dori Laub argues that distorted memory and untold stories are endemic to Holocaust representation. W.G. Sebald inscribes this distortion into his narratives, calling attention to but also repeating its effects. I argue that a perspective beginning with (but not limited to) a combined reading of these three texts yields a more complete understanding of trauma and the Holocaust than can be offered by any singular genre—even archives of documented testimonies, which, despite their necessary role, are unavoidably fraught with a problematics of memory itself.